Prevalence and risk factors of burnout among employees at COVID-19 vaccination centers: A cross-sectional study - Alaa Mathkour; Abdullah Hassan Alzahrani; Bayapa Reddy Narapureddy; Faris Maeed Alqahtani; Abdullah M. Alshehri; Majed Atiah Althagafi; Shmookh Mohsen Alsyd; Shaik Mohammed Asif; Sunil Kumar Vaddamanu (PLoS ONE, 2025)
Background Health care workers working in Covid-19 vacciantion centers due to their exponential demand experience burnout and stress. Burnout, a psychological syndrome is characterized by emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA). It can adversely affect professional and personal well being of an individual. Aim of this study was to check prevalence of burnout among health care workers, to identify personal and work-related factors, and to compare the risk factors associated with the different dimensions of burnout (EE, DP, and PA). Methods This cross-sectional study was carried out among 180 employees of various COVID-19 vaccination centers. Three dimensions of burnout (EE, DP, and PA) were evaluated usinge Maslach Burnout Inventory (MBI), and association between burnout and other factors were assessed using logistic regression analysis with 95% confidence intervals (CI). Results Prevalence rate of burnout among health care workers was 73.3%. Emotional exhaustion being the highest dimension (38.4%) followed by Depersonalization (30.8%) and personal accomplishment (33.1%). Young employees (<30 years) had significantly higher prevalence of burnout compared to old employees (82.4% vs. 52.4%, p = 0.033). Additionally, employees working more than 8 hours/day (OR = 9.98, p = 0.032) and employess with less than 6 hours of sleep/night (OR = 0.39, p = 0.042) had more likely to experience burnout. Conclusion There was an increase prevalence rate of burnout observedamong employees at COVID-19 vaccination centers. There was a significant association between personal and work-related factors such as age, working hours, and sleep patterns. Addressing these factors, particularly by promoting better work-life balance and mental health support, is essential to mitigate burnout and improve employee well-being.